Metodologia para mitigação de desligamentos intempestivos em linhas de transmissão correlacionados a umidade elevada - Puchale, Leandro Henrique Bona (Universidade do Vale do Rio dos Sinos, 2019)
This work deals about the development of methodology to mitigate the problem of unplanned outage in transmission lines, more specifically of transitory nature, that occur in normal operation regime and non-adverse climatic conditions. This problem is observed with greater intensity in transmission lines composed of ceramic insulators (glass or porcelain) and during in wet conditions. The hypothesis analyzed in this dissertation is that the wetting ability of these insulators may cause the formation of a water film that, combined with the contamination on the surface of the insulator, results in momentary flashover in the string. Different methods developed by researchers, companies and manufacturers are used to improve the performance of insulators under these conditions. The application of RTV (Room Temperature Vulcanizing) silicone coating on glass insulation is a method that already shows good results in several countries. This practice combines the mechanical and dielectric strength of the ceramic insulators with the hydrophobicity of the water repellent polymer surface, thus reducing the leakage current and the consequent possibility of disruptive discharge (transmission line outage). The scope of this research is to analyze the performance of the implementation of four (4) different configurations of insulators string with RTV in a transmission line that operates in 230 kV as a solution to mitigate transient outages. The performance of the new configurations is evaluated by comparing the number of outages occurring at the installation locations of each type of configuration, before and after such deployment. In general, the results obtained with the new configurations show the improvement in performance, mainly reflecting the RTV's effectiveness in relation to humidity / contamination. In addition, during the line monitoring stage it was observed that some transient outages have still occurred, not due to the moisture / contamination effect of the insulators surface, but due to a peculiar mechanism caused by birds: the bird streamer. In this context, the methodology developed is characterized by practical applicability, and may serve as a reference for the mitigation of transient outages in transmission lines of other utilities in the electric sector.
Keywords: Desligamento; Falha Transitória; Linha de Transmissão; Descarga disruptiva; Isolador; RTV; Outage; Transient fault; Transmission line; Flashover; Insulator; RTV; ACCNPQ::Engenharias::Engenharia Elétrica